2021
DOI: 10.1007/s13679-021-00423-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Bariatric Surgery in Adolescents

Abstract: Purpose of Review The prevalence of obesity is increasing in all age groups. Following its success in adults, and with limited success using conservative therapies, metabolic and bariatric surgery (MBS) is increasingly being utilized in adolescents. This review highlights the current evidence and guidelines supporting its use. Recent Findings Safety and efficacy mirror results seen in adults. The most recent evidence, as outcomes enter the long term, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“… 40 Obesity will progress from childhood to adulthood without effective intervention, followed by a series of expanding related physical and mental health problems. 41 We found that stress management behavior and life appreciation behavior scores of NWNO female students were significantly higher than those of the NWO, and these two indicators remarkably negatively correlated with BF%. Regression analysis revealed that the risk of NWO was lower in females with a higher score in stress management behavior, which was consistent with the previous researches that stress had been shown as a key risk factor affecting obesity, 42 and psychological stress in the family led to childhood obesity.…”
Section: Discussionmentioning
confidence: 60%
“… 40 Obesity will progress from childhood to adulthood without effective intervention, followed by a series of expanding related physical and mental health problems. 41 We found that stress management behavior and life appreciation behavior scores of NWNO female students were significantly higher than those of the NWO, and these two indicators remarkably negatively correlated with BF%. Regression analysis revealed that the risk of NWO was lower in females with a higher score in stress management behavior, which was consistent with the previous researches that stress had been shown as a key risk factor affecting obesity, 42 and psychological stress in the family led to childhood obesity.…”
Section: Discussionmentioning
confidence: 60%
“…Many patients consider bariatric surgery to address their obesity [20][21][22][23]. Variation in the type of bariatric surgery that is used can depend on the surgeon and the site that the surgery is performed.…”
Section: Possible Solutions To the Problems Associated With Obesitymentioning
confidence: 99%
“…Several recognized post-operative complications may require further operative procedures, particularly symptomatic gallstone disease and small bowel obstruction. The rate of reoperation in the 5 years after RYGB appears to be slightly higher in adolescents than that in adults (20–25%) [ 67 ]. However, recent improvements in operative technique and post-operative management have led to substantial reductions in the major causes of reoperation after bariatric surgery [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of reoperation in the 5 years after RYGB appears to be slightly higher in adolescents than that in adults (20–25%) [ 67 ]. However, recent improvements in operative technique and post-operative management have led to substantial reductions in the major causes of reoperation after bariatric surgery [ 67 ].…”
Section: Introductionmentioning
confidence: 99%